A New Method Based on Exhaustion for Immobilization of Silver Nanoparticles on The Surface of Cotton Fabrics - YAZDANSHENAS, M.E.; SHATERI KHALILABAD, M.; NATEGHI, M.R. (Asian Journal of Chemistry, 2010)
This work explores the antibacterial activity, yellowness and whiteness indices of cotton fabric pretreated with nano-silver colloidal solution. A new method based on exhaustion is introduced to deposit nano-silver particles on the surface of cotton fabric samples. By this way, the antibacterial properties of the fabrics due to the binding of silver nanoparticles are conserved for long time. Nano-silver colloidal solution has been used to treat the fabric samples by exhaustion method at 80 ºC in various concentration of nano-silver. Effect of radiation at different exposition time durations on the yellowness and whiteness indices has been studied. Present study showed that antibacterial activities of fabric samples depend on the amount of silver deposited on the surface of the fabric and it was recognized that even at low concentration of silver, samples showed good antibacterial effect and very good durability to washing. Yellowness index was increased with increasing of silver content and irradiation time intervals but whiteness index decreased. These deficiencies can be reduced by washing samples before exposing to light.